Recount Text in EFL Vocational School: A Thematic Structure Analysis - Amartya, Dini; Nugraha, Sidik Indra; Ridwan, Iwan (Universitas Lancang Kuning, 2022)
Recount text is a staple material taught in the first year of Indonesian secondary schools yet research on this dominant ELT unit is limited despite the common observation of many students struggling to produce a well-written recount text. To address this research gap and problem, this study conducted a textual meaning analysis in the texts written by tenth-grade Vocational School. This study aimed to figure out the types of themes shown in 14 recount texts written by 14 students from two different vocational schools with other majors. The approach used the content analysis method and belonged to descriptive qualitative research. Content analysis is used as the technique to analyse the data considering Eggins’ 1994 Systemic Functional Linguistics (SFL) theory. The analysis revealed that most of the themes used are Unmarked Topical Themes. Every student has a different way of delivering messages in the Recount text that they made. Moreover, the researchers found Marked Topical Theme, Mood Adjunct Interpersonal Theme, Conjunction Textual Theme, Conjunctive Textual Theme, Continuative Textual Theme, and Multiple Theme. The result of the present study is hoped to provide insights, gained from observing patterns of Theme and Rheme relations, for secondary English teachers’ endeavours to help improve students’ cohesion.